Correction - Kaluža, Jernej (Javnost-The Public, 2022)
Article title: Habitual Generation of Filter Bubbles: Why Is Algorithmic Personalisation Problematic for the Democratic Public Sphere? Author: Jernej Kaluža Journal: Javnost – The Public DOI: http://dx.doi.org/10.1080/13183222.2021.2003052 When the above named article was first published, the authorship of the book Updating to Remain the Same: Habitual New Media (Cambridge, MA: The MIT Press, 2016) was incorrectly given as Wendy Chun and Hui Kyong. The authorship of the book has now been corrected throughout the article to Wendy Hui Kyong Chun.